“Sou ou não sou uma estrela?” Impacto do ‘boca a boca’ nas redes sociais no sucesso de um filme: Análise da Trilogia X de Ti West - Pereira, Raffaella Urquiza Araujo (Universidade Federal de São Carlos, 2025)
The objective of this study is to investigate the influence of conversations on social media, the "digital word of mouth," on a film's commercial success. With the impact of streaming and the growing presence of social media in the entertainment sector, it is necessary to reassess the concept of success in cinema, as before this digital transformation, the main metric for a film's success was box office performance, whereas now these market factors require new perspectives. Through a historical contextualization of film marketing, the research explores the industry's strategies from the 2000s to the present, highlighting how technological changes have impacted the industry and how these changes have affected consumer behavior. In order to explore these new aspects of the sector, the research will focus on the actions of A24 due to its recent prominence in the market, where the studio developed innovative digital strategies through the strategic use of social media, systematizing a digital-focused promotional model that other studios in the sector now follow. Based on this, the research will address the challenges posed by the lack of transparency in streaming data and the absence of an effective method to relate the real impact of social media on a film's audience. These challenges highlight the difficulty of establishing a new metric that can accurately measure the success of an audiovisual work in today's market. To exemplify these issues, the research will discuss the distinct impacts that social media conversations had on the commercial performance of the films Barbie (2023) and Morbius (2022). In conclusion, the thesis will use all this contextualization and hypothesis development to analyze the research's object of study, the film series X (2022–2023) directed by Ti West and distributed by A24. For this object, the study will examine the impact that the viral success of one of its films, Pearl, had on the anticipation of its sequel, MaXXXine. This analysis will aim to understand the relevance of social media word-of-mouth for the commercial performance of the film that concludes the trilogy, MaXXXine.
“Am I a star or not?” The impact of word of mouth on social media on a film’s success: Analysis of Ti West’s X Trilogy
Keywords: Earned media; A24; Streaming; Marketing cinematográfico; Trilogia X; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA